2000
DOI: 10.1016/s0885-3924(99)00139-6
|View full text |Cite
|
Sign up to set email alerts
|

Topical Capsaicin in the Management of HIV-Associated Peripheral Neuropathy

Abstract: Distal symmetrical peripheral neuropathy (DSPN) is a particularly distressing pain syndrome associated with human immunodeficiency virus (HIV) disease. Capsaicin has been found to be effective in relieving pain associated with other neuropathic pain syndromes, and is mentioned as a possible topical adjuvant analgesic for the relief of DSPN. This multicenter, controlled, randomized, double-masked clinical trial studied patients with HIV-associated DSPN and compared measures of pain intensity, pain relief, senso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
64
0
5

Year Published

2003
2003
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(69 citation statements)
references
References 37 publications
0
64
0
5
Order By: Relevance
“…Oral capsaicin in a candy (taffy) vehicle produced substantial temporary pain reduction in 11 patients with oral mucositis pain from cancer therapy (44). However, capsaicin was not effective in relieving pain accompanying HIV-associated distal symmetrical peripheral neuropathy (45).…”
Section: The Paradox Of Topical Application Of Capsaicinmentioning
confidence: 99%
“…Oral capsaicin in a candy (taffy) vehicle produced substantial temporary pain reduction in 11 patients with oral mucositis pain from cancer therapy (44). However, capsaicin was not effective in relieving pain accompanying HIV-associated distal symmetrical peripheral neuropathy (45).…”
Section: The Paradox Of Topical Application Of Capsaicinmentioning
confidence: 99%
“…Four studies identified (Basha 1991;Donofrio 1991;Scheffler 1991;Tandan 1992) were reports of parts of a multicentre study (CSG 1992), only one of which (Tandan 1992, 22 participants) provided any additional data. Eleven other studies were excluded after reading the full report (Chad 1990;Fusco 1992;McCarty 1994;McCleane 2000;Paice 2000;Peikert 1991;Pfeifer 1993;Robbins 1998;Vickers 1998;Watson 1988;Watson 1989). Reasons for exclusion are in the 'Characteristics of excluded studies' table.…”
Section: Description Of Studiesmentioning
confidence: 99%
“…Similarly, investigator or physician reported outcomes do not reliably correspond to patient outcomes. In particular, four studies of 4 weeks' duration were excluded (Chad 1990;McCarty 1994;McCleane 2000;Paice 2000). These studies enrolled 329 participants, 90 of whom were treated with 0.075% capsaicin, and 21 with 0.025% capsaicin.…”
Section: Overall Completeness and Applicability Of Evidencementioning
confidence: 99%
“…Topical capsaicin is generally not considered a satisfactory sole therapy for chronic pain conditions and is often considered an adjuvant to other approaches (Watson, 1994). No significant benefit was reported in chronic distal painful neuropathy (Low et al, 1995) or with human immunodeficiency virus-neuropathy (Paice et al, 2000).…”
Section: Capsaicinmentioning
confidence: 99%